CEM JUEGO version 3.0 : gamification learning for civil engineering measurement works / Norbaizura Abu Bakar ... [et al.] - Abu Bakar, Norbaizura; Abdul Tharim, Asniza Hamimi; Ismail, Nur’Ain; Othman, Muhammad Anas; Hussin, Siti Nurhayati; Jaffar, Noraidawati; Muhamad, Nurul Huda (Universiti Teknologi MARA, Kedah, 2023)
The Construction Industry Development Board Malaysia (CIDB) 2013 has promoted the Civil Engineering Standard Method of Measurement (MyCESMM) to avoid discrepancies and ambiguities in the bill of quantities (BQ) for civil engineering works. Hence, it becomes challenging for students to grasp the knowledge and principles of MyCESMM. Gamification is a new teaching and learning technology that create excellent opportunities for creative approaches to improving knowledge and collaboration among students. The 1st and 2nd versions of CEM JUEGO board game were introduced to increase engagement, collaboration, and excitement of students in the class as well as developed fun learning for the students and lecturers by upgrading the features of the board game. Therefore, CEM JUEGO version 3.0 attempts to innovate the board game feature by transforming the card game questions into the paperless system using online platforms. This game is played by four (4) players within two (2) hours of time allocation in the class. The students are required to answer all questions online in the game and evaluation will be done by using the developed rubric. Consequently, this concept of scan and play could contribute to a paperless system while promoting environmental sustainability. CEM JUEGO Version 3.0 has the potential for commercialization among civil engineering beginners as well as other institutions which offer civil engineering courses in teaching and learning. It is hoped that this game will enhance their knowledge in an entertaining and engaging way to interpret the basic principles in measuring stipulated civil engineering works based on the current MyCESMM.